Thai music emotion recognition based on western music - S Sangnark; M Lertwatechakul; C Benjangkaprasert (My University, 2019)
Music emotion recognition is the music emotion detected from people's annotations. In this paper, the Thai music was the evaluated set of a system based on western music training settings. By using valence-arousal values, multiple linear regression, k-nearest neighbours to represent the emotional annotations from the music. We used valence and energy(arousal) from Spotify API to the investigated emotion of Thai music. As a result, the Thai music emotion according to the western music criteria could be understood. The highest f-measure of Thai music from multiple linear regression All feature was 41% and the f-measure of western music from multiple linear regression without tempo feature was 51 %, which are very different because All feature in western music is low efficiency than other models.
Keywords: Feature (linguistics); Western music; Music and emotion; Music and Audio Processing